Cognitive Evaluation in Sports and Esports: A Comparative Guide to Performance Testing (Spor, Egzersiz ve Performans Dergisi, 2026)
Purpose: Cognitive processes we use all the time in every aspect of our lives are particularly critical in traditional sports and esports for rapid information processing. While there are existing studies in the literature on cognitive tests conducted with traditional and e-sports athletes, this review aims to synthesize these studies to provide systematic information for sports coaches and athletes on which cognitive performance to develop for each sport, using computer-based cognitive tests. The tests used in this review article are from PEBL software, which aims to measure cognitive processes that begin with the sensory perception of environmental stimuli, are transferred to short-term memory, and then to task-dependent working memory via attention. The cognitive processes used in this review were examined in five different ways: (1) Attention and Alertness, (2) Inhibitory Control, (3) Cognitive Flexibility and Executive Functions, (4) Memory Systems, (5) Decision Making and Risk, and (6) Time Perception Assessment. This review aims to raise awareness among traditional and esports coaches by bridging theoretical cognitive psychology and applied sports sciences. By introducing the cognitive test batteries frequently used in the PEBL battery and discussing the task in detail, this work aims to serve as a resource for developing cognitive assessments and targeted cognitive training interventions for traditional and digital athletes.